Reshaping the Curriculum for Academy in Factory in Malaysia - Jamaludin, Khairul Azhar; Ealangov, Suganti; Saleh, Siti Nur Haslinda Md; Zabidi, Nor’Aqilah Ahmad; Alias, Norlidah; Yasin, Mohd Hanafi Mohd; Alias, Bity Salwana (Frontiers in Psychology, 2023)
Academy in Factory (AiF) was recently introduced in Malaysia to cater to the talent development and education attainment for a future-ready workforce. Though ideally expected to be an effective initiative, a lack of a strong curriculum framework hinders its implementation. To date the literature on AiF is very limited. It was found that its vague definition and characteristics, non-harmonized interaction between industry and academia, and non-existing curriculum framework are among contributing factors to its ineffective implementation. Thus, this study is aimed at reshaping a curriculum framework that is responsive to its aims and objectives. Building upon an extensive review of literature on AiF, industry-based curriculum, employability and human capital development, and best practices in the international context, the proposed framework is hoped to serve as a reference to improve its current practice.